Recent Advances in the Synthesis and Medicinal Chemistry of SF5 and SF4Cl Compounds - Sani, Monica; Zanda, Matteo (Synthesis, 2022)
This short review covers the most important advances published in the literature during the last five years, concerning the synthesis, chemical modifications, and applications of SF5 and SF4Cl compounds in medicinal/bioorganic chemistry and materials science.1 Introduction2 Methods for Incorporation/Manipulation of SF4Cl/SF5 Groups2.1 Nonaromatic SF5 Compounds via Direct Pentafluorosulfanylation of Alkenes and Alkynes2.2 SF4Cl- and SF5-Aryl/Heteroaryl Derivatives3 Synthesis of SF5/SF4Cl/SF4-Substituted Small Molecules3.1 Heterocycles3.2 Amines and Amino Acids3.3 α-SF5 ketones3.4 Miscellaneous Alkyl-, Alkenyl-, and Aryl-SF5 Compounds4 Medicinal/Biological Applications4.1 Anticancer Compounds4.2 Antibacterial and Antiparasitic Compounds4.3 Central Nervous System4.4 Miscellaneous Biological Activity5 Materials Science Applications6 Conclusion
Keywords: pentafluorosulfanyl; chlorotetrafluorosulfanyl; synthesis; applications; materials Science; medicinal Chemistry; biological activity